The importance of prenatal in basic health: a bibliographic review (Research, Society and Development, 2021)
The beginning of prenatal care took place in the 20th century, when the health of women and fetuses was a worrying factor, since until then maternal and infant mortality rates were high; however, the purpose of pré-christmas care was to reduce these rates. This present study aimed to analyze the monitoring of pré-christmas care and its challenges in Basic Health Units, as well as to analyze which actions are recommended for the care of pregnant women, and to investigate the incentive policies for pré-christmas. This is a literary review, in which, for the theoretical basis, articles and scientific texts on the descriptors related to the subject were selected (Primary Care; Prenatal; Women's Health). Thus, even with certain risks, special moments in a woman's life are considered, pregnancy, childbirth and the puerperium, which are physiological events that develop in a cultural and social context. In this context, for pré-christmas to be considered adequate and with treatment and monitoring that aims to be holistic, it is necessary that it beearly and diligent, in addition to having specialized professionals Who perform treatments, hospitalizations and examinations if necessary. Brazil is a developing country and even though access is not linear, it is important that professionals help pregnant women in the best way possible. Furthermore, pré-christmas tends to in crease the chances of a more relaxed pregnancy and childbirth, with minimized risks, with early treatment being possible, avoiding sequelae and promoting a safer childbirth.